2016
DOI: 10.1097/pep.0000000000000216
|View full text |Cite
|
Sign up to set email alerts
|

Use of the TIMP in Assessment of Motor Development of Infants With Down Syndrome

Abstract: The TIMP is a sensitive measure of delayed motor development in infants with DS and can be used to confirm the need for therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Malak et al 20 carried out a study with DS children in which the researchers confirmed that the upstanding and gait skills were delayed even when physiotherapy was performed. Other studies on the first months of DS children, however, revealed the vital importance of interventional treatments in the multiple areas of motor development 21,22 .…”
Section: Discussion Interpretationmentioning
confidence: 99%
“…Malak et al 20 carried out a study with DS children in which the researchers confirmed that the upstanding and gait skills were delayed even when physiotherapy was performed. Other studies on the first months of DS children, however, revealed the vital importance of interventional treatments in the multiple areas of motor development 21,22 .…”
Section: Discussion Interpretationmentioning
confidence: 99%
“…Impaired neuro-psychomotor development of children with DS is related to low muscle tone and difficulties in postural control and balance [3][4][5] . The child with DS has intrinsic limitations, such as muscle hypotonia and joint hypermobility, which collaborate for the motor impairment, slowness of movement and postural control changes 6 .…”
Section: Introductionmentioning
confidence: 99%